Síntese in situ de nanopartículas de ouro para obtenção de compósitos com polissacarídeos visando aplicações biomédicas - Almeida, Débora Aparecida de (2019)
The composites production based on polysaccharide and gold nanoparticles (AuNPs) has been the focus of many current research. It has been reported that the materials of this nature has bactericidal and anti-carcinogenic properties, besides serving as matrices for cell growth. Natural polysaccharides, such as chitosan and pectin, usually exhibit low cytotoxicity and are biocompatible. Then, they are suitable for use in the production of biomaterials. In addition, the hydrogels obtainment with these polysaccharides has been widely reported. The pectin/chitosan hydrogels can be excellent matrices for AuNPs because their 3D-organized chains can be able to perform an in situ synthesis as well as provide a stable environment for the nanomaterial. Based on this, the present work is a simple method to obtain pectin-AuNPs/chitosan composites, which was tested as a matrix for cell growth. Initially, it was an in situ synthesis of AuNPs in pectin solution by mixing the gold precursor (HAuCl4) with the polysaccharide under heat at 65°C. Different concentrations of polysaccharide and HAuCl4 solutions were tested. Then, pectin-AuNPs hydrogels and 1% (w/v) chitosan, diluted in 0,1 mol.L-1 HCl, were also obtained at 65°C. As the pectin AuNPs were characterized by spectroscopy, surface resonance bands localized to AuNPs were highlighted. The compounds were characterized by infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), scanning electron microscopy (SEM) and zero charge point (pHpcz), as companies have proven their success. The disintegration assay by injection in PBS showed that the pectin-AuNPs/chitosan association allowed the production of stable hydrogels in the ratio 60:40 pectin-AuNPs:chitosan (B0 and B3), when pectin 2,5% (w/v) and 1% (w/v) chitosan solutions were used with and without AuNPs included in the 3D matrix . The hydrogels, without the addition of HAuCl4 (B0), showed swelling around 4500%. The composites had approximately 3000%, when the largest amount of gold precursor was tested. The presence of AuNPs made the hydrogels more rigid. Cell growth tests showed that the composite presented 84% cell viability for ADSC cells compared to positive control (titanium plate). This indicates that the material produced has favorable properties for application in the biomedical area of tissue renewal. It is noteworthy that the path of obtaining the composite, considering the in situ synthesis of AuNPs in pectin followed by conjugation with chitosan, has not yet been reported in the literature.